(untitled) - Olds, Elizabeth Fagg (New York, NY, 1985)
Annie Smith Peck attempted seven times to climb Peru's highest mountain; Delia Akeley hunted big game in Africa; Marguerite Harrison spied in Russia for America; Louise Arner Boyd led expeditions to perilous East Greenland. Precursors of the modern Jane Goodalls and Sally Rides, these women represent a fascinating but forgotten era in the literature of exploration.
Keywords: Explorers, women,Explorers; Biography,Biography; United states